Collective sensemaking for action: researchers and decision makers working collaboratively to strengthen health systems. (15th February 2021) - Gilson, Lucy; Barasa, Edwine; Brady, Leanne; Kagwanja, Nancy; Nxumalo, Nonhlanhla; Nzinga, Jacinta; Molyneux, Sassy; Tsofa, Benjamin
Abstract : Lucy Gilson and colleagues draw on experiences from Kenya and South Africa to consider the practice, benefits, and challenges of research co-production for strengthening health systems